2011
DOI: 10.1021/jo201095p
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity DNA Targeting Using Readily Accessible Mimics of N2′-Functionalized 2′-Amino-α-L-LNA

Abstract: N2′-Pyrene-functionalized 2′-amino-α-L-LNAs (Locked Nucleic Acids) display extraordinary affinity toward complementary DNA targets due to favorable preorganization of the pyrene moieties for hybridization-induced intercalation. Unfortunately, the synthesis of these monomers is challenging (~20 steps, <3% overall yield), which has precluded full characterization of DNA-targeting applications based on these materials. Access to more readily accessible functional mimics would be highly desirable. Here we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(84 citation statements)
references
References 51 publications
7
76
0
1
Order By: Relevance
“…17b Thus, treatment of O 2, O 2′-anhydrouridine 1 20 with tris(pyren-2-yl)methyl borate or tris(pyren-4-yl)methyl borate - generated in situ 21 via addition of 2-pyrenemethanol 22 or 4-pyrenemethanol 23 to borane - afforded 2Y and 2Z in modest but acceptable yields (30% and 20% respectively, Scheme 1). Subsequent O5′-dimethoxytritylation gave nucleosides 3Y and 3Z , which upon treatment with 2-cyanoethyl- N , N -diisopropylchlorophosporamidite (PCl reagent) and Hünig’s base provided target phosphoramidites 4Y and 4Z in excellent yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17b Thus, treatment of O 2, O 2′-anhydrouridine 1 20 with tris(pyren-2-yl)methyl borate or tris(pyren-4-yl)methyl borate - generated in situ 21 via addition of 2-pyrenemethanol 22 or 4-pyrenemethanol 23 to borane - afforded 2Y and 2Z in modest but acceptable yields (30% and 20% respectively, Scheme 1). Subsequent O5′-dimethoxytritylation gave nucleosides 3Y and 3Z , which upon treatment with 2-cyanoethyl- N , N -diisopropylchlorophosporamidite (PCl reagent) and Hünig’s base provided target phosphoramidites 4Y and 4Z in excellent yield.…”
Section: Resultsmentioning
confidence: 99%
“…16 The resulting probes display similar dsDNA-recognition efficiency and are much easier to synthesize. 17,18 Identification of these simple building blocks allowed us to initiate systematic structure-property relationship studies with the goal of gaining additional insights into the structural determinants governing Invader recognition efficiency. For example, we demonstrated that all four canonical 2′- O -(pyren-1-yl)methyl-RNA monomers can be used to construct dsDNA-binding Invader probes.…”
Section: Introductionmentioning
confidence: 99%
“…Our group found the initial O3′,O5′-tritylation of uridine to be cumbersome and therefore devised an alternative route 12 to key intermediate 3 that is based on trialkylborate 13 mediated ring opening of O2,O2′-anhydrouridine 6 using 1-pyrenemethanol in anhydrous DMSO at high temperatures (Scheme 2). Key intermediate 3 is obtained in slightly higher overall yield (~18% vs ~23%) and this route is, in our opinion, more practical across a wider range of reaction scales.…”
Section: Synthesis Of 2′-o-(pyren-1-yl)methyl Rna Building Blocksmentioning
confidence: 99%
“…As it is frequently observed with intercalator-modified ONs, 14,17,26 mismatched DNA targets are less efficiently discriminated than with unmodified reference strands. While S2 and O2 display similar binding fidelity, significantly better discrimination is observed with N2 .…”
mentioning
confidence: 89%
“…We hypothesized that the lower electronegativity of the sulfur atom of 2′- S -(pyren-1-yl)methyl-2′-thiouridine monomer S would weaken the gauche effect between O4′ and the 2′-substituent, and thus increase the population of C2′- endo ( South -type) furanose conformations. 16 This, in turn, was expected to result in more favorable conditions for pyrene intercalation, leading to higher cDNA affinity relative to ONs modified with current-generation Invader building blocks 2′- O -(pyren-1-yl)methyluridine monomer O 17 or 2′- N -(pyren-1-yl)methyl-2′- N -methyl-2′-aminouridine monomer N 17 (Figure 1). …”
mentioning
confidence: 99%